2017
DOI: 10.1103/physrevb.95.104434
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous spin-orbit torque switching in synthetic antiferromagnets

Abstract: We report that synthetic antiferromagnets (SAFs) can be efficiently switched by spin-orbit torques (SOTs) and the switching scheme does not obey the usual SOT switching rule. We show that both the positive and negative spin Hall angle (SHA)-like switching can be observed in Pt/SAF structures with only positive SHA, depending on the strength of applied in-plane fields. A switching mechanism directly arising from the asymmetric domain expansion is proposed to explain the anomalous switching behaviors. Contrary t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 53 publications
5
43
0
Order By: Relevance
“…Bi et al observed this behavior Figure 6. Qualitative reproduction of the experimental results of Bi et al 22 The sign of the relative velocity of walls with (Q 1 , Q 2 ) = (+1, −1) and (Q 1 , Q 2 ) = (−1, +1) can be toggled only by changing the magnitude of the applied field. We use the material parameters supplied in the third column of Table I. in SAF structures for small in-plane fields, but by toggling between large and small values of the in-plane field (same sign), they were able to toggle the sign of the relative velocity of the walls and thereby the favored magnetization direction.…”
Section: B Novel Switching Behavior In Saf Structuressupporting
confidence: 61%
“…Bi et al observed this behavior Figure 6. Qualitative reproduction of the experimental results of Bi et al 22 The sign of the relative velocity of walls with (Q 1 , Q 2 ) = (+1, −1) and (Q 1 , Q 2 ) = (−1, +1) can be toggled only by changing the magnitude of the applied field. We use the material parameters supplied in the third column of Table I. in SAF structures for small in-plane fields, but by toggling between large and small values of the in-plane field (same sign), they were able to toggle the sign of the relative velocity of the walls and thereby the favored magnetization direction.…”
Section: B Novel Switching Behavior In Saf Structuressupporting
confidence: 61%
“…The dynamics of synthetic antiferromagnets is also relevant for switching by spin-orbit torques that has recently been demonstrated in devices containing synthetic antiferromagnetic layers. 19,20 .…”
Section: Statics and Dynamicsmentioning
confidence: 99%
“…Furthermore, the synthetic antiferromagnetic exchange coupling enhances the stability of the chiral Neel domain walls, thereby allowing much larger SOTs for the same current density, and therefore higher domain wall velocities. SOT‐induced magnetization switching of synthetic antiferromagnets was also reported …”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 78%